Upper Cretaceous dinosaur nesting sites of Río Negro (Salitral Ojo de Agua and Salinas de Trapalcó-Salitral de Santa Rosa), northern Patagonia, Argentina - Salgado, Leonardo (2007)
Twenty three different sites in two areas of Río Negro Province (Salitral Ojo de Agua and Salitral de Santa Rosa-Salinas de Trapalcó), preserving eggs and eggshells from the Allen Formation (Upper Cretaceous) were studied, and five egg levels were identified. Three different types of eggshell were recognized. Eggs possessing thick eggshells of Type 1 are abundant in both areas, sometimes associated with eggs having thinner shells. Eggs of eggshell Type 1 are included in the oofamily Faveoloolithidae of the parataxonomic classification. Eggshell Type 2 is subdivided into two groups (Types 2A and 2B), mostly based on the mean thickness of the eggshells and other parameters. Eggs of eggshell Type 2 are assigned to the oofamily Megaloolithidae of the parataxonomic classification, and ascribed to titanosaurs. A third type of eggshell (Type 3) is only recorded at one of the localities (Salitral Ojo de Agua, egg level 2). This type is intimately associated with theropod bones, and its microstructure agrees with an assignation to the Theropoda. It is assigned to the oofamily Elongatoolithidae.